Coronary sinus atrial septal defect without persistent left superior vena cava: Three-dimensional imaging of a rare defect - Sean Del-Rossi Quadros; Sreeja Pavithran; Ravi Agrawal; Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2018)
Coronary sinus defects refer to interatrial communications that lie out of the confines of the atrial septum and leads from left to right shunt through the ostium of the coronary sinus. When associated with persistent left superior vena cava (PLSVC), mild systemic desaturation may occur depending on the extent of unroofing of the coronary sinus. Isolated defects without PLSVC are rare. Three-dimensional echocardiographic and surgical images are presented.